Preclinical Evaluation of 99mTc-ZHER2:41071, a Second-Generation Affibody-Based HER2-Visualizing Imaging Probe with a Low Renal Uptake; International Journal of Molecular Sciences; Vol. 22, iss. 5 - Oroujeni M. Maryam; Rinne S. S. Sara; Vorobjeva (Vorobyeva) A. G. Anzhelika Grigorjevna; Loftenius A. Annika; Feldwisch J. Joachim; Jonasson P. Per; Chernov V. I. Vladimir Ivanovich; Orlova A. M. Anna Markovna; Frejd F. Y. Fredrik; Tolmachev V. M. Vladimir Maksimilianovich (2021, 2021)
Radionuclide imaging of HER2 expression in tumours may enable stratification of patients with breast, ovarian, and gastroesophageal cancers for HER2-targeting therapies. A first-generation HER2-binding affibody molecule [99mTc]Tc-ZHER2:V2 demonstrated favorable imaging properties in preclinical studies. Thereafter, the affibody scaffold has been extensively modified, which increased its melting point, improved storage stability, and increased hydrophilicity of the surface. In this study, a second-generation affibody molecule (designated ZHER2:41071) with a new improved scaffold has been prepared and characterized. HER2-binding, biodistribution, and tumour-targeting properties of [99mTc]Tc-labelled ZHER2:41071 were investigated. These properties were compared with properties of the first-generation affibody molecules, [99mTc]Tc-ZHER2:V2 and [99mTc]Tc-ZHER2:2395. [99mTc]Tc-ZHER2:41071 bound specifically to HER2 expressing cells with an affinity of 58 ± 2 pM. The renal uptake for [99mTc]Tc-ZHER2:41071 and [99mTc]Tc-ZHER2:V2 was 25–30 fold lower when compared with [99mTc]Tc-ZHER2:2395. The uptake in tumour and kidney for [99mTc]Tc-ZHER2:41071 and [99mTc]Tc-ZHER2:V2 in SKOV-3 xenografts was similar. In conclusion, an extensive re-engineering of the scaffold did not compromise imaging properties of the affibody molecule labelled with 99mTc using a GGGC chelator. The new probe, [99mTc]Tc-ZHER2:41071 provided the best tumour-to-blood ratio compared to HER2-imaging probes for single photon emission computed tomography (SPECT) described in the literature so far. [99mTc]Tc-ZHER2:41071 is a promising candidate for further clinical translation studies.